The Key Technology of Oblique Photogrammetry of Assembled Buildings by UAV. (7th October 2022) - Yao, Jian; Na, Jiaming; Ma, Rong; Wang, Yuyan
Abstract : In order to ensure the disaster control during infrastructure construction and operation, a method of tilt photogrammetry of prefabricated buildings using UAV is proposed. A comparative study of the key steps in the 3D construction process of building (structure) was carried out, and a set of 3D morphology construction method based on UAV tilt photogrammetry was proposed, and the key steps were optimized to realize automation and visualization in the process of model construction. The experimental results show that in the application case of a school district, the error of the three directions is distributed between -4 cm and 4 cm, accounting for 74%, and that between -2 cm and 2 cm, accounting for 37%; the root mean square error of the three directions was calculated to be 4.0 cm, 3.8 cm, and 2.8 cm, respectively. In an engineering application case, the error size of the three directions distributed between -4 cm and 4 cm accounted for 74%, and that between -2 cm and 2 cm accounted for 50%; the root mean square error of the three directions was calculated as 2.3 cm, 2.5 cm, and 3.3 cm, respectively. Conclusion . This method can not only obtain high-precision 3D models of urban complex and single buildings, but also meet the requirements of digital city construction for 3D model construction and obtain clear and high-precision digital land surface model.